Analisis Kinerja Karyawan Pada Pelayanan Kesehatan Di Rumah Sakit Umum Daerah Lubai Ulu Kabupaten Muara Enim Tahun 2023 - Aspebri Cahyadi; Chairil Zaman; Lilis Suryani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Health services in hospitals are carried out to improve the quality and safety of patients. Seeing the importance of patient safety, hospital management must ensure that every employee is always at their best performance in carrying out their duties and responsibilities. The low performance of employees in providing services will build a poor assessment of health services, where patients will not be satisfied and will share their experiences with their friends. This quantitative research is an analytic observational study with a cross-sectional design that aims to analyze the performance of employees in health services at Lubai Ulu Hospital, Muara Enim Regency in 2023. This research was conducted at Lubai Ulu Hospital, Muara Enim Regency which was conducted on June 5-27 2023. The sample in this study were employees at Lubai Ulu Hospital, Muara Enim Regency in 2023 as many as 63 people. Data collection using a questionnaire. The results of this study indicate that the factor related to employee performance is motivation (p value = 0.031). Meanwhile, age (p value=0.065), gender (p value=0.160), education (p value=1.000), knowledge (p value=0.288), training (p value=1.000), income (p value=1.000), attitude (p value=0.282), leadership style (p value=0.467) and length of service (p value=0.872) are not related to employee performance. The results of the multivariate analysis show that motivation is the dominant factor influencing employee performance (p value=0.036). The results of this study indicate that the performance of employees at Lubai Ulu Hospital is influenced by motivation. For this reason, Lubai Ulu Hospital needs to increase employee motivation by increasing regular training, giving rewards or additional incentives.